Accounting professionalism and local government gaap adoption: A national study. Issue 2 (1st March 2014) - Khumawala, Saleha; Marlowe, Justin; Gordon Neely, Daniel
Abstract : We examine the factors that associate with local government decisions to comply with Generally Accepted Accounting Principles (GAAP). GAAP non-compliance is surprisingly common among larger local governments, and that trend has important implications for public policy, financial management transparency, and government accountability. To examine the factors that drive GAAP compliance, we develop a conceptual framework based on the politico-economic perspective on accounting policy choice, and then test that model with data from a national survey of local government finance professionals. Our key contribution is that we incorporate accounting professionalism. The findings suggest that for many local governments the decision to adopt GAAP is a response to the pressures of professionalism rather than a rational response to political and economic motives.